Vukovar - poslednji rez - Baljak, Janko (Serbia and Montenegro : Matic, Veran ; Kranjac, Vanja, 2006)
A painstaking investigation into the history of the 1991 Vukovar tragedy. Why was it that Vukovar, a rich Slavonian town famous as a "miniature Yugoslavia", Tito's exemplary town of unity, was the one location to suffer total apocalypse, one comparable to the sacrifice and siege of Stalingrad, and by the extent of destruction, and scenes shown around the world, reminiscent of Hiroshima and Nagasaki? Why was a city which had neither strategic importance nor a strong military presence in the conflict between the Yugoslav National Army and the Croatian military, so systematically destroyed while the Serbian (Milosevic) and Croatian (Tudjman) leaders walked around Tito’s estate, discussing plans for a new division of Yugoslavia? With the help of the survivors and available archives, a Serbian director and Croatian journalist put together the pieces of this impossible mosaic. This film is neither a Serbian documentary nor a Croatian one. It is the first Serbian-Croatian co-production about this painful topic, whose wounds have yet to heal, even after a lapse of fifteen years.
Duration: 01:43:00
Keywords: Documentary films